Business Security Threat Overview Using IT and Business Intelligence - Thaduri, Upendar Rao (Global Disclosure of Economics and Business, 2017)
Through a critical reflection on how information systems (IS) are currently defined in the IS literature, this study aims to contribute to a more profound knowledge of information systems (IS). The research identifies a number of definitions of IS that may be found in the literature by employing the hermeneutic method for literature reviews. The examination of these definitions allows for the differentiation of four distinct perspectives on information systems (IS): a technology view, which emphasizes the technological aspects of IS; a social theory, which highlights the sociocultural factors of IS; a socio-technical view, which emphasizes the interconnection of technology and social elements; and a process view, which emphasizes the activity orientation of IS. This study critically examines the many methods of understanding and conceptualizing information systems and explores their contributions and limits. Based on this examination, the paper argues for developing an alternative socio-material understanding of IS based on a non-dualist, relational ontology.